Bioactivities of Malvaviscus arboreus var. drummondii and Phyllanthus reticulatus Poir. (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The study was designed to evaluate the bioactivities of crude methanol extracts of leaves of Malvaviscus arboreus and Phyllanthus reticulatus along with their pet-ether, carbon tetrachloride, chloroform and aqueous soluble partitionates. The antioxidant potential was evaluated by DPPH and Folin-Ciocalteau reagents using butylated hydroxytolune (BHT) and ascorbic acid as standards. In the DPPH free radical scavenging assay, the crude methanol extract of M. arboreus revealed the highest free radical scavenging activity with IC50 values 6.47 ± 0.78 ?g/ml. In brine shrimp lethality bioassay, the chloroform soluble materials of M. arboreus displayed the highest cytotoxic potential having LC50 values 2.73 ± 0.36 ?g/ml, whereas the standard vincristine sulphate exhibited an LC50 value of 0.45 ?g/ml. In the thrombolytic activity assay, the pet-ether soluble fractions of M. arboreus and P. reticulatus revealed 55.60 ± 0.48 % and 18.99 ± 0.84% clot lysis, respectively. In the membrane stabilizing activity assay, the chloroform soluble fraction of M. arboreus inhibited heat- and hypotonic solution- induced haemolysis of RBCs by 54.60 ± 0.81 % and 66.96 ± 0.84 % as compared to 57.06 % and 72.79 % inhibition by acetyl salicylic acid (0.10 mg/ml), respectively. On the other hand, the pet-ether soluble materials of crude methanol extract of P. reticulatus demonstrated 57.11 ± 0.57 % and 70.62 ± 0.22 % inhibition of heat- and hypotonic solution- induced hemolysis, respectively. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21892 Dhaka Univ. J. Pharm. Sci. 13(2): 143-147, 2014 (December)